(untitled) (المجلة العراقية للعلوم الاقتصادية, 2018)
A Suggested Method to Estimate the Potential Output Potential output is the level of output that can be produced at a level of full employment. The importance of potential output that it’s reflects the level of output that can be produced without undesired inflation. Then the policy maker will be able to depend on the level of potential output in relation with the level of actual output (or what might be called output gap) as an indicator of loss in production capacity when it exceeds the actual level of potential output. Otherwise, it means a stress on the resources, and may lead to inflationary pressures when there is no flexibility in the possibility of production, or may lead to an additional catalytic effect of the economy when there is complete flexibility in the possibility of production. As a result of the importance of the potential output variable and depending on the logic of economic theory, the research has tried to device an easy way, different from the ways that depend on a complex time series ways. The devised method has been applied on the Iraqi economy, and the significant results were obtained.